Empagliflozin prohibits high-fructose diet-induced cardiac dysfunction in rats via attenuation of mitochondria-driven oxidative stress - Bugga, Paramesha; Mohammed, Soheb Anwar; Alam, Md Jahangir; Katare, Parmeshwar; Meghwani, Himanshu; Maulik, Subir Kumar; Arava, Sudheer; Banerjee, Sanjay Kumar (Life sciences (1973), 2022)
SGLT2 inhibitors show promising cardio-protection in the diabetic populace. However, the defending effect of SGLT2 inhibition in diabetes-associated cardiac complications and the molecular mechanism behind this effect are not thoroughly studied. Therefore, we aimed to investigate the effect of Empagliflozin, an SGLT2 inhibitor, in type-2 diabetic rat hearts. We induced type-2 diabetes in SD rats by giving a high-fructose diet for 20 weeks. We administered Empagliflozin (10 mg/kg p.o.) daily from the 12th week to the 20th week, along with high-fructose diet. We weighed the cardiac structure and function by echocardiography, electrocardiography, and blood pressure in diabetic rats. Other parameters like cardiac fibrosis, oxidative stress, and mitochondrial dynamics by protein expression were measured. To simulate a similar in-vivo condition, we persuaded insulin resistance in H9c2 cells by palmitic acid (PA) treatment. We then examined glucose uptake, cellular ROS, mitochondrial ROS and membrane potential in the presence and absence of Empagliflozin treatment. We saw a significant perturbation of the majority of the parameters associated with cardiac structure and function in high-fructose diet-induced diabetic rats. We found that administration of Empagliflozin improved all the perturbed parameters by attenuating insulin resistance, oxidative stress, and cardiac fibrosis and also by promoting cardiac mitochondrial fusion in high-fructose diet-induced type-2 diabetic rats. Empagliflozin also reduced palmitate-induced insulin resistance, total cellular ROS, and mitochondrial ROS in H9c2 cells. Our study concluded that SGLT2 inhibition with Empagliflozin prevented the high-fructose diet-insulted cardiac function by suppressing insulin resistance and oxidative stress and promoting mitochondrial fusion.